EFFECTIVENESS OF NPK 15-15-15 FERTILIZER COMBINED WITH EGG SHELL FLOUR ON THE GROWTH OF OIL PALM (ELAEIS GUINEENSIS JACQ.) SEEDLINGS: EFEKTIVITAS PUPUK NPK 15-15-15 YANG DIKOMBINASIKAN DENGAN TEPUNG CANGKANG TELUR TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis Guineensis Jacq.) - Mizar Liyanda; Maghfirah, Maghfirah; Mulyanti; Ika Rezvani Aprita; Sri Agustina; Nurlaela (PT. ROCE WISDOM ACEH, 2026)
Oil palm (Elaeis guineensis Jacq) is a domesticated plant with promising industrial potential in domestic and international markets. This study aims to determine the effect of a 15-15-15 NPK fertilizer mixture and eggshell powder on the growth parameters of oil palm seedlings. This study used a non-factorial randomized block design (RAK) with 5 treatments and 5 replicates, resulting in 25 experimental units, with the following treatment sequence: P0: Control (without fertilizer) NPK 15-15-15 and eggshell flour, P1: NPK 15-15-15 fertilizer (2 g/polybag) + 50 g eggshell flour, P2: NPK 15-15-15 fertilizer (2.25 g/ polybag) + 50 g eggshell powder, P3: NPK 15-15-15 fertilizer (2.50 g/polybag) + 50 g eggshell powder, P4: NPK 15-15-15 fertilizer (2.75 g/polybag) + 50 g eggshell powder. The parameters observed were soil pH, number of leaf sheaths, plant height, and stem diameter. The results showed that the NPK 15-15-15 treatment combined with eggshell flour had a significant effect on stem diameter at 40 DAP but no significant effect on stem diameter growth at 50-60 DAP, on the number of leaf sheaths, on plant height, or on soil pH. The coefficient of variation obtained was below 25%.